2022
DOI: 10.1038/s41598-022-25949-x
|View full text |Cite
|
Sign up to set email alerts
|

Data quality evaluation in wearable monitoring

Abstract: Wearable recordings of neurophysiological signals captured from the wrist offer enormous potential for seizure monitoring. Yet, data quality remains one of the most challenging factors that impact data reliability. We suggest a combined data quality assessment tool for the evaluation of multimodal wearable data. We analyzed data from patients with epilepsy from four epilepsy centers. Patients wore wristbands recording accelerometry, electrodermal activity, blood volume pulse, and skin temperature. We calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 77 publications
(96 reference statements)
2
27
1
Order By: Relevance
“…Because this would be highly subject dependent, it is unclear whether there is a general pattern that can be guaranteed in this regard, but it is an important psychological effect that was not accounted for in the present study. Some observers believe that the use of wearables or implanted seizure detectors 38 may allow for more accurate measurement of long‐term seizure rates, although such ideas would present considerable technical, 39 financial, and psychological 40 challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this would be highly subject dependent, it is unclear whether there is a general pattern that can be guaranteed in this regard, but it is an important psychological effect that was not accounted for in the present study. Some observers believe that the use of wearables or implanted seizure detectors 38 may allow for more accurate measurement of long‐term seizure rates, although such ideas would present considerable technical, 39 financial, and psychological 40 challenges.…”
Section: Discussionmentioning
confidence: 99%
“…that the use of wearables or implanted seizure detectors 38 may allow for more accurate measurement of long-term seizure rates, although such ideas would present considerable technical, 39 financial, and psychological 40 challenges.…”
Section: Limitationsmentioning
confidence: 99%
“…Second, our study design utilized streaming data, potentially resulting in fewer headaches fulfilling the headache data ratio requirement due to missing data. Böttcher et al (2022) observed that using the Empatica E4 in a non-streaming mode generally yields a higher data ratio, but streaming results in a lower user burden as patients do not have to manually download the data from the device and send it to…”
Section: Limitationsmentioning
confidence: 99%
“…Signal artifacts and noise in PAD data pose another substantial challenge, as factors such as motion artifacts, variable environmental conditions, battery life, user engagement, or electronic interference can affect data quality (Böttcher et al, 2022;Onnela, 2021). PAD accuracy and reliability is still a concern, especially since issues like data missingness or quality are not comprehensively reported in current MRI-PAD studies.…”
Section: There Is An Increasing Interest In Combining Mri and Portabl...mentioning
confidence: 99%